Catalytic methane decomposition over ZrO2 supported iron catalysts: Effect of WO3 and La2O3 addition on catalytic activity and stability. (August 2020) - Al -Fatesh, Ahmed Sadeq; Kasim, Samsudeen Olajide; Ibrahim, Ahmed Aidid; Al-Awadi, Abdulrhman S.; Abasaeed, Ahmed Elhag; Fakeeha, Anis H.; Awadallah, Ahmed E.
Abstract: A leading method of hydrogen production that is free of carbon oxides is catalytic methane decomposition. In this research, Fe supported catalysts produced by wet impregnation method were employed in the methane decomposition. The effect of doping ZrO2 with La2 O3 and WO3 on the catalytic performance was studied. Different techniques were used to characterize the catalysts. It was discovered that support doped with WO3 gave the best performance in terms of CH4 conversion, H2 yield and stability at the test condition (800 ° C, 4000 ml/hgcat space velocity). The initial H2 yield was found to be 58%, 81% and 92% on Fe/ZrO2, Fe/La2 O3 –ZrO2 and Fe/WO3 –ZrO2 catalysts, respectively. These values were significantly decreased to reach 20% and 25% over the Fe/ZrO2 and Fe/La2 O3 –ZrO2 catalysts after running for 240 min. On the contrary, the Fe/WO3 –ZrO2 catalyst maintained its catalytic activity and stability within the reaction time. The BET results showed remarkable increase in the specific surface area of Fe/La2 O3 +ZrO2 and Fe/WO3 +ZrO2 compared to Fe/ZrO2 catalyst. TPR profiles revealed progressive change in the valency of Fe in its combined form to the zero valence free metal. The Fe/WO3 –ZrO2 catalyst showed the highest reduction temperature among the tested catalysts, probably due to the strong metal support interaction. The Fe/WO3 –ZrO2 gave the best performance and maintained stability during the time on stream. Its stability was attributed to the higher dispersion and stabilization of iron nanoparticles on the surface of WO3 –ZrO2 support. TEM and TPO results indicated that the deposited carbon was multi-walled carbon nanotubes with tabular structure. Graphical abstract: Image 1 Highlights: Zirconia supported iron catalysts were studied for methane decomposition reaction. The addition of WO3 enhanced the activity and stability of the Fe/ZrO2 catalyst. Methane conversion of as high as 90% was obtained over Fe/WO3 –ZrO2 catalyst.